Clarifying the typification of the names Kalanchoe fedtschenkoi and K. waldheimii (Crassulaceae subfam. Kalanchooideae), two leaf-succulent shrubs indigenous to Madagascar - Smith, Gideon F.; Shtein, Ronen (Phytotaxa, 2021)
N/A